The Influence of KAP Reputation, Ethics, Integrity, and Auditor Experience on Audit Quality (Case Study on Public Accounting Firms in Jakarta Area) - Nanditya Andini; Cris Kuntadi; Rachmat Pramukty (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2025)
The purpose of this study was to determine whether KAP reputation, ethics, integrity, and auditor experience affect audit quality at public accounting firms in the Jakarta area. The population in this study were auditors who worked at public accounting firms in the Jakarta area. The sampling technique used was purposive sampling method. The sample used in this study were auditors who worked at 8 public accounting firms in the Jakarta area with a total of 46 respondents. The data used in this study are primary data obtained from questionnaires distributed directly and sent via gform by researchers to auditors in KAP who have been sampled for research. The analysis method of this research uses the Statistical Package for Social Science (SPSS) software version 25. This hypothesis was tested using descriptive statistical analysis, classical assumption test, multiple linear regression analysis test, and hypothesis testing. The results of this study indicate that (1) KAP reputation has a positive effect on audit quality (2) ethics has no effect on audit quality (3) integrity has no effect on audit quality (4) auditor experience has a positivet effect on audit quality.